The girl who slept with God [large type] - Brelinski, Val (Thorndike Press, 2015)
For fans of Celeste Ng's Everything I Never Told You and Meg Wolitzer's The Interestings comes an entrancing literary debut about religion, science, secrets, and the power and burden of family from recent Wallace Stegner Fellow Val Brelinski.